The threshold of gravity in the crime of aggression: a new category in the illicit use of force? (Editor) - Pezzano, Luciano (Anuario Iberoamericano de Derecho Internacional Penal, 2021)
In this essay we will refer to the effects on international standards on the use of force may be called "threshold of gravity" found in the definition of the crime of aggression in article 8 bis of the Rome Statute. Emphasizing the gravity as a defining characteristic of aggression, we will seek to determine whether the threshold of Article 8a introduces a new category within the illicit use of force. To do this, we aggression in the context of international standards on the use of force and the provisions of Article 8a, in particular, the threshold clause, references to resolution 3314 (XXIX) of the General Assembly United Nations and "understandings" approved by the Review Conference. (editor)